The Influence of Graduates' Competence from Universitas Darussalam Gontor on the Relevance Level between Fields of Study and Employment - Niayatulloh, Ahmad; Haikal, Muhammad; Rochmadi, Idris (Pusat Publikasi Nusantara, 2024)
The success of higher education institutions is often measured by their competitiveness and the quality of their graduates in the job market. The concept of competitiveness, particularly in terms of educational relevance, is a fundamental consideration outlined in Law No. 12 related to higher education. One of the mechanisms for assessing this educational relevance involves conducting tracer studies among graduates. The objective of this research is to examine the individual (partial) and combined (simultaneous) effects of Grade Point Average (GPA) and Academic Supporting Credit for Students (AKPAM) on the alignment between graduates' fields of study and their subsequent employment. This study focuses on alumni from Darussalam Gontor University in the year 2019. The research is conducted through a survey-based approach, and the data collected through tracer study questionnaires. The findings indicate that while GPA exhibits an insignificant influence on the degree of alignment between fields of study and employment, AKPAM significantly affects this alignment. Moreover, when considered together, both GPA and AKPAM exert a significant influence on the alignment between graduates' fields of study and their employment choices